2017
DOI: 10.5152/imj.2017.85866
|View full text |Cite
|
Sign up to set email alerts
|

Which Approach is Preferred in Spinal Anesthesia: Median or Paramedian? Comparison of Early and Late Complications

Abstract: Spinal anesthesia is often preferred in short-term surgeries because it is a low-cost technique that can be applied easily, has a high success rate, and allows fast mobilization and early feeding (1). The side effects in this application can vary with the technique that is used (2). Inadequate spinal anesthesia, high or total spinal block, cardiac arrest, respiratory arrest, systemic toxic reaction, hypotension, bradycardia, nausea/vomiting, headache, spinal puncture pain, meningitis or meningismus, neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…In contrast, Rabinowitz et al 8 found that the success rate was 85% with the PA and 45% with the MA in their study in which 40 patients were included. In other similar studies, the success rate was found to be 100% with the PA and 90% with the MA 9,10 . In this study, the success rate was found to be 90.5% with the PA and 79.1% with MA, which is similar to studies 9,10,12 .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In contrast, Rabinowitz et al 8 found that the success rate was 85% with the PA and 45% with the MA in their study in which 40 patients were included. In other similar studies, the success rate was found to be 100% with the PA and 90% with the MA 9,10 . In this study, the success rate was found to be 90.5% with the PA and 79.1% with MA, which is similar to studies 9,10,12 .…”
Section: Discussionmentioning
confidence: 65%
“…However, it was stated that longer spinal needles should be used for the PA. The success rate was found to be 90% with the PA and 70% with the MA by Sing et al 9 , 92% with the PA and 68% with the MA by Ali et al 7 , and 60% with the by Ahsan ul-haq et al 10 . In our study, the attempt from another space due to failure was not statistically significant, however, it was more with the MA.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Contrary to this, Nisar A et al 17 who studied 100 pregnant patients undergoing caesarean section under spinal block, concluded that incidence of spinal headache was higher with paramedian approach. A study conducted by Bayindir S and colleagues 5 in Turkey compared the early and late complications associated with median versus paramedian approach, found no statistically significant difference between the two. However, the study was not restricted to any specific age group.…”
Section: Discussionmentioning
confidence: 96%
“…Thus the technique of applying spinal block and experience matters to avoid such drawbacks. 5 It is usually performed by midline approach. While using the midline approach at the desired level the needle passes through skin, subcutaneous tissue, supraspinous ligament, interspinous ligament ligamentum flavum, epidural space, dura mater, arachnoid mater and finally subarachnoid space.…”
Section: Introductionmentioning
confidence: 99%